Генеза формування концептуальних засад східного напрямку зовнішньої політики республіки Польща - Яковлева, І. В.; Яковлева, И. В.; Jakovleva, I. (My University, 2013)
Article is dedicated to the conceptual basis of formation of Polish foreign policy, in particular – its east. Analyzed historical, pragmatic and geopolitical dimensions of the evolution of the eastern direction of foreign policy of the Republic of Poland. It is noted that at certain stages of its genesis determined «pyastovska», «Jagiellonian», «inkorporatyvna», «federal» concept, and the concept of «Giedroyc-Myeroshevskoho», «Map-84», East European cooperation.
Яковлева І. В. Генеза формування концептуальних засад східного напрямку зовнішньої політики республіки Польща / І. В. Яковлева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 284-289.
Keywords: концептуальні засади формування польської зовнішньої політики; східний напрямок зовнішньої політики Польщі; зовнішня політика Польщі; еволюція східного напрямку зовнішньої політики Польщі; визначальні концепції східного напрямку зовнішньої політики Польщі; восточное направление внешней политики Польши; внешняя политика Польши; эволюция восточного направления внешней политики Польши; определяющие концепции восточного направленяи внешней политики Польши; концептуальные основы формирования польской внешней политики; Conceptual bases of formation of Polish foreign policy; eastern direction of Polish foreign policy; Polish foreign policy; the evolution of the eastern direction of Polish foreign policy; defining the concept of the eastern direction of Polish foreign policy